Depression : law and ethics - Foster, Charles, 1962-; Herring, Jonathan (Oxford : Oxford University Press, 2017)
If the law is to regulate the lives of those who suffer from depression, it is vital that lawyers understand the condition. This edited collection outlines the questions that arise from cases of depression by drawing together viewpoints from lawyers, philosophers, clinicians, and first-hand accounts from sufferers.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 15, 2017).
Keywords: Depressed persons -- Legal status, laws, etc. -- Great Britain; Depression, Mental; Depression, Mental -- Moral and ethical aspects; Medical laws and legislation -- Great Britain; Medical ethics; Law; Laws of specific jurisdictions & specific areas of law